GENOTOXICITY EVALUATION OF SALICYLIC ACID IN POTATO CULTIVARS INOCULATED WITH POTATO VIRUS YNTN USING ISSR MARKERS - SHERIN A. MAHFOUZE,; HEBA A. MAHFOUZE, (International Journal of Pharma and Bio Sciences, 2016)
Salicylic acid (SA) acts a fundamental function in plant viruses' resistance and hypersensitive cell death. In addition, it is involved in hardening reactions to abiotic stress. The aim of the work was to address the following questions. 1- Is SA treatment causes genotoxicity and DNA damage in potato cultivars and wild species inoculated with Potato virus YNTN (PVYNTN)? 2- Is treatment of both SA and PVYNTN affect antioxidant enzymes in potato? In this study, it is shown that total activities of polyphenol oxidase (PPO) and peroxidase (POX) increased upon potato cultivars treatment with a mixture of virus inoculum and SA (SA+V) and/or PVYNTN infection (V). The inter-simple sequence repeats (ISSR) analysis was used to evaluate the genotoxic effect on four potato cultivars and one wild type treated mixture of SA and PVYNTN (SA+V) compared with the control. ISSR profiles showed that SA+V treated cultivars were having low genotoxic effects on potato. This was discernible with appearance/disappearance of bands in the treatments compared with the control. A total of 84 ISSR amplified fragments were obtained using five primers, out of which 28 were polymorphic (33.33%) and 56 were monomorphic (66.67%). SA+V treatment induced 19 new bands (22.62% polymorphism). Nei’s genetic similarity index calculated between the treated cultivars and control was clustered in two groups. The first group I: (genetic similarity 0.83 to 0.93) and the second groups II: (genetic similarity 0.75 to 0.92). This indicates that SA+V treatment is less genotoxic. Therefore, it could be concluded that 2 mM SA had not caused significance DNA damage to potato cultivars; it could be used in viral diseases resistance without having harmful effect on human and the environment.